Juridical Review of Law Number 14 of 2008 concerning Public Information Disclosure on Transparency in Village Fund Management - Mardeli, Iis (JLASA (Journal of Law and State Administration), 2025)
This study aims to analyze the juridical implementation of Law Number 14 of 2008 on Public Information Disclosure (PID Law) in promoting transparency in village fund management. The research employs a normative juridical method with statutory and conceptual approaches. The results indicate that the PID Law provides a strong legal foundation for village governments to uphold the principles of transparency, accountability, and public participation in managing public funds. However, its implementation at the village level still faces several challenges, including limited understanding among village officials, the suboptimal role of Village Information and Documentation Officers (PPID), and inadequate information infrastructure. Therefore, strengthening derivative regulations and enhancing the legal capacity of village apparatus are essential. The enforcement of public information disclosure principles is expected to create transparent, participatory, and accountable village governance in accordance with the ideals of good governance.